A microfluidic platform for simulating stem cell migration using in vivo-like gradients of stem cell mobilizer - Kim, Jin; Kim, Jinyoung; Park, Hyun Ji; Jeon, Eun Je; Cho, Seung Woo (Korean Journal of Chemical Engineering, 2023)
Stem cell mobilization by cytokines and peptide drugs contributes to wound healing in injured tissues. Owing to the short half-life of cytokines and short peptides in vivo, precisely predicting the in vivo therapeutic efficacy of stem cell mobilizers is difficult using current in vitro models. To address this problem, we developed a multichannel microfluidic device with diffusion barriers to recapitulate drug gradients in an in vivo-like environment. We investigated the effects of Substance P (SP), a stem cell mobilizer, on the migration of human bone marrow-derived mesenchymal stem cells (BM-MSCs) in the microfluidic chip, which replicated in vivo drug gradients. Simulations of SP concentration indicated that our microfluidic chip established SP gradients in migration channels, unlike the existing scratch model for cell migration assays. The scratch model did not distinguish the effects of SP with a short half-life and PEGylated SP with an extended half-life on BM-MSC migration, whereas the microfluidic system demonstrated that PEG-SP affected BM-MSC migration more than SP. Furthermore, the microfluidic chip allowed accurate quantification of the distance and direction of BM-MSC migration. Our microfluidic system could be useful for the precise evaluation of drugs associated with cell migration and mobilization.
Keywords: Cell Migration; Drug Gradient; Microfluidic Chip; Stem Cell Mobilization; Substance P